The Influence of Hotel’s Website Brand and Quality on Consumers Trust and Purchasing Interests (A Case Study at Maca Group, Bali) - Kadek Dwi Mahesayasa; Ida Ayu Putri Widawati; Irene Hanna H. Sihombing; Ni Wayan Pastini (International Journal of Applied Research in Tourism and Hospitality, 2022)
Website is one of the revenue channels that must be optimized to gain more transactions and acknowledgment to consumers. Good website quality and brand will gain the trust of consumers which will gain their buying interest. The purpose of this research will be as follows: analyze the influence of website brands on consumer trust and buying interest, analyze the influence of website quality on consumer trust and consumer buying interest, analyze the influence of trust on consumer buying interest, and analyzes the role of trust in conciliating website brand on consumers buying interest and website quality on consumers buying interest. The location of this study is Maca Group. This study uses a quantitative approach. Data were collected by distributing questionnaires to 100 guests who made reservations as respondents. The results of data analysis with SmartPLS show that: website brand has a positive influence on trust and buying interest, website quality has a positive influence on consumers trust and buying interest, trust has a positive influence in conciliating website brand on buying interest and website quality on buying interest.